URGENSI PEMBAHARUAN HUKUM KEIMIGRASIAN DALAM MENGATASI PEMALSUAN DATA OLEH WARGA NEGARA ASING UNTUK MEMPEROLEH PASPOR REPUBLIK INDONESIA (STUDI KASUS KC WNA SINGAPURA PADA KANTOR IMIGRASI KELAS I TPI PEKANBARU) - Aji, Koesmoyo Ponco; Guchi, Hadi Mulia; Utami, Devina Yuka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The right of individuals to enter or leave a territory is a fundamental human right that is inherently attached to every person. However, the exercise of this right must be balanced with corresponding obligations to ensure the protection of others' rights—one of which involves the rights and responsibilities associated with obtaining travel documents. This study focuses on one such travel document issued by the Republic of Indonesia: the Indonesian Passport (Paspor RI). The falsification of civil registry data by a Singaporean national in the process of acquiring an Indonesian passport constitutes a misuse of the state administrative system, which poses a threat to the legitimacy of immigration documents. The weak integration of verification systems between the Directorate General of Immigration and the Directorate General of Population and Civil Registration (Dukcapil) creates legal loopholes that may be exploited by foreign nationals to unlawfully obtain citizenship or immigration documents. This research aims to analyze the urgency of reforming immigration law, both substantively and administratively, in order to evaluate legal gaps that have not yet addressed these issues and to propose legal reforms that can resolve the problems in the Indonesian passport issuance process. The method used is normative, employing statutory and comparative legal approaches. The findings indicate that Law No. 6 of 2011 does not yet specifically regulate effective cross-sectoral verification mechanisms or impose specific sanctions on foreign nationals who falsify civil data. Therefore, legal reform is needed in the form of additional provisions concerning system integration and the strengthening of administrative criminal sanctions as a systemic preventive measure.